Social-Educational Factors of Children’s Citizenship Education in Basic School: the Context of Lithuania - Malinauskienė, Daiva; Vaitkevičienė, Asta; Bražienė, Nijolė; Širiakovienė, Asta; Masiliauskienė, Erika (Social Welfare: Interdisciplinary Approach, 2023)
Citizenship education is a relevant issue of education and international policy in many countries, including Lithuania, especially due to the current tense geopolitical situation. In 2022-2023, after updating general education curricula, citizenship education competence is included in all subjects of general education. According to the updated Fundamentals of Citizenship programme for grades 9–10, students can develop citizenship competences by participating in nonformal education and engaging in other activities related to citizenship education. To achieve the aim of the research presented in the article – to analyze the social-educational factors of children’s citizenship education in basic school – an empirical study was carried out, for which the Diagnostic Questionnaire for the Situation of Citizenship Education by Valuckienė et al. (2017) was used. The study made it possible to distinguish the social-educational factors important for citizenship education: the child’s trust in the school staff, the child’s relationship with community events, adults’ respect for the child’s opinion, the child’s interest in news and the child’s participation in school self-government. The results of the empirical study confirmed the hypotheses: 1) respect for the child’s opinion is moderately positively related to the child’s involvement in the life of the school community, participation in school self-government and 2) adults’ respect for the child’s opinion is weakly positively related to the child’s trust in the school staff.